Leadership Communication Strategies in Building Corporate Culture for Organizational Transformation in the National Healthcare Equipment Industry - Maddi, Jaenal Hasyim; Tomasowa, Gloria Angelita (Eastasouth Institute, 2025)
Organizational change is a necessity for companies that seek to remain competitive, particularly in the national healthcare equipment industry. A strong corporate culture plays a crucial role in supporting organizational transformation. One of the key factors in building an adaptive culture is leadership communication. This study examines how leadership communication styles—including vertical, horizontal, and transformational communication—can assist healthcare equipment companies in managing change and enhancing employee engagement. The study explores challenges in establishing effective communication and the outcomes of implementing communication strategies that support a strong corporate culture. Based on the analysis conducted, it was found that open and adaptive leadership communication can increase employee loyalty, improve work efficiency, and accelerate adaptation to technological and regulatory changes. Therefore, it is essential for healthcare equipment companies to develop transparent communication systems and provide communication training for leaders to manage change more effectively.